2015
DOI: 10.1155/2015/104048
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions of Dew and Scavenging of Particles in Changchun, China

Abstract: Dew and rain water were collected during 2013 and 2014 in Changchun, China. The dew was analyzed and the following parameters were measured: pH, EC, TDS, major anions (F−, Cl−,SO42-, andNO3-), and major cations (NH4+, Na+, K+, Ca2+, and Mg2+). The mean pH, EC, and TDS values of dew were comparable with the values for rainwater. The pH values of dew and rain were 6.72 and 6.16, respectively. Both EC (308 μS/cm) and TDS (154 mg/L) of dew were higher than those in rain samples. The concentration of main ions in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…3), Paris rain being slightly more acidic than dew. This corresponds to the results found in some other urban areas as well as at humid sites (Xu et al, 2015 Tables 2-3).…”
Section: Dew and Rain Yieldssupporting
confidence: 91%
“…3), Paris rain being slightly more acidic than dew. This corresponds to the results found in some other urban areas as well as at humid sites (Xu et al, 2015 Tables 2-3).…”
Section: Dew and Rain Yieldssupporting
confidence: 91%
“…The average pH of dew at RMNP was 5.19 (median = 5.34), which is on the lower range of what has been reported for dew. For instance, Yaalon and Ganor (1968) and Xu et al (2015) found median dew pH of 7.7 and 6.72 in Jerusalem and Changchun, China, respectively, whereas Pierson et al (1986) reported an average dew pH of 4.0 at a rural site in Pennsylvania in a region containing several coalfired power plants. Given the remoteness of RMNP and low ionic concentrations, CO 2 dissolution plays an important role in governing dew pH.…”
Section: Dew Parametersmentioning
confidence: 99%
“…Over the last 5 decades, several dozen studies have characterized dew composition and have found that NH + 4 is a ubiquitous constituent of dew and, in some environments, can be the most abundant cation (e.g. Polkowska et al, 2008;Wagner et al, 1992;Yaalon and Ganor, 1968;Yadav and Kumar, 2014). Average [NH + 4 ] reported in dew ranges from 25 µM (Lekouch et al, 2010) to 1600 µM (Yadav and Kumar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under wet conditions, these acids tend to partition to wet ecosystem surfaces inducing a downward flux, while under dry conditions, water films or droplets dry out and release acids to the atmosphere, thereby causing an upward flux. While simple solubility suggests that these volatile acids would dominantly remain in the gas phase, dew is often more alkaline than natural water, or water equilibrated with ambient CO 2 (dew pH > pKa for these acids) (Lekouch et al, 2010; Muselli et al, 2002; Takeuchi et al, 2002; Xu et al, 2015). The subsequent acid‐base equilibria will enhance partitioning from the atmosphere to the aqueous phase, as will additional hydrolysis chemistry or reactions.…”
Section: Hncomentioning
confidence: 99%